Upaya Meningkatkan Kemampuan Numerasi Anak Usia Dini dengan Metode Pembelajaran Kolaboratif Usia 5-6 Tahun di TK Darut Tauhid Balung - Ruba’iyyah, Siti; Zahro, Ianatuz; Adhim, Fauzan (Universitas Nusantara PGRI Kediri, 2024)
One of the most important aspects of everyday life is numeracy. Increasing children's numerical abilities at an early age will have a positive impact on their academic abilities later in life. The aim of this research is an effort to improve the numeracy skills of early childhood children aged 5-6 years at Darut Tauhid Kindergarten. This research uses the classroom action research (PTK) method with the Kemmis and Mc Taggart model which consists of four steps, namely planning, implementation, observation and reflection. Data analysis uses qualitative descriptive analysis techniques. The criteria for research success is increasing numeracy skills in children aged 5 to 6 years, if it reaches a minimum of 71% of children developing as expected or developing very well. Based on the results of the actions, it can be concluded that children's numeracy abilities increase with each cycle. This is proven by an increase in the percentage of children's numeracy abilities from 60% with a total of 12 children in the category developing according to expectations and developing very well in cycle I, increasing in cycle II by 80% with a total of 16 children in the same category. This shows that collaborative learning methods are effective when applied during learning, especially to improve the numeracy skills of early childhood.